Chitosan- and Alginate-Based Hydrogels for the Adsorption of Anionic and Cationic Dyes from Water - Sanchez-Poblete, J; Alsamman-, M (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Novel hydrogel systems based on polyacrylamide/chitosan (PAAM/chitosan) or polyacrylic acid/alginate (PAA/alginate) were prepared, characterized, and applied to reduce the concentrations of dyes in water. These hydrogels were synthetized via a semi-interpenetrating polymer network (semi-IPN) and then characterized by Fourier transformed infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA), and their swelling capacities in water were measured. In the adsorption experiments, methylene blue (MB) was used as a cationic dye, and methyl orange (MO) was used as an anionic dye. The study was carried out using a successive batch method for the dye absorption process and an equilibrium system to investigate the adsorption of MO on PAAM/chitosan hydrogels and MB on PAA/alginate in separate experiments. The results showed that the target hydrogels were synthetized with high yield (more than 90%). The chemical structure of the hydrogels was corroborated by FTIR, and their high thermal stability was verified by TGA. The absorption of the MO dye was higher at pH 3.0 using PAAM/chitosan, and it had the ability to remove 43% of MO within 10 min using 0.05 g of hydrogel. The presence of interfering salts resulted in a 20-60% decrease in the absorption of MO. On the other hand, the absorption of the MB dye was higher at pH 8.5 using PAA/alginate, and it had the ability to remove 96% of MB within 10 min using 0.05 g of hydrogel, and its removal capacity was stable for interfering salts. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.